Sociology of Mental Health
XVI, 159 p. 6 illus.
Keywords: This volume provides an overview of mental health research conducted by sociologists. It discusses dominant themes such as stress, the community and mental life, family structure, social relations and recovery. The unique contribution of sociology to the study of mental health has a long history stretching from the very foundations of modern sociology. Yet it was only twenty years ago that the Section on Sociology of Mental Health of the American Sociological Association was formed largely in response to a burgeoning rise in the sum and significance of research in the field. Today the section is a large and vibrant one with its own journal, Society and Mental Health. This book explores several of the themes that have occurred during that period, providing both perspectives of the past and prospects for the future. The volume is timely, following closely the 20th anniversary of the section’s formation. Its coverage of key issues and its advancement of the scholarly debates on these issues will prove valuable to students and senior scholars alike.